High-temperature-resistant SiOC-SiO2 ceramic nanofiber aerogel and preparation method thereof

Through the method of combining SiOC-SiO2 ceramic nanofibers and silicon sol, a high-temperature resistant ceramic nanofiber aerogel was prepared, which solved the problem of structural collapse of ceramic aerogels in high temperature environments, and achieved long-term use at high temperatures of 1300℃ and high-efficiency oxidation resistance.

CN119859068APending Publication Date: 2025-04-22YANGTZE DELTA REGION INST (QUZHOU) UNIV OF ELECTRONIC SCI & TECH OF CHINA
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202411921406.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2025-04-22

AI Technical Summary

Technical Problem

Existing ceramic aerogels are prone to crystallization and powderization in extremely high temperature environments, resulting in structural collapse and are difficult to apply to high-temperature aerobic conditions.

Method used

A ceramic nanofiber aerogel was prepared by electrospinning and high-temperature pyrolysis by combining SiOC-SiO2 ceramic nanofibers and high-temperature binder silicon sol, and a dense insulation layer was formed through the silicon sol to inhibit the oxidation of SiOC.

Benefits of technology

It improves the high temperature resistance of the aerogel, so that it can be used for a long time in an extremely high temperature environment of 1300℃, has extremely strong oxidation resistance, and simplifies the preparation process and reduces costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859068A_ABST
    Figure CN119859068A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of nano-porous materials, provides high-temperature-resistant SiOC-SiO2 ceramic nanofiber aerogel and a preparation method thereof, and aims to solve the problem of poor thermal stability of conventional aerogel under extremely high-temperature conditions so as to improve the application performance and stability of the aerogel in a high-temperature environment. According to the main scheme, the preparation method comprises the following steps: mixing tetraethyl orthosilicate and methyltrimethoxysilane, hydrolyzing to prepare a spinning solution, preparing nanofibers by adopting electrostatic spinning, and pyrolyzing to obtain SiOC-SiO2 ceramic nanofibers; and adding the obtained fibers into a high-temperature binder, and carrying out directional freezing casting, vacuum drying and high-temperature calcination to form the aerogel. The prepared ceramic nanofiber is of a SiOC and SiO2 co-inlaid composite structure, and the structure can effectively inhibit rapid growth of silicon dioxide grains in a high-temperature environment, so that the high-temperature resistance of the aerogel is improved. In the preparation process of the aerogel, silica sol is attached to the surfaces of the SiOC-SiO2 ceramic nanofibers to form a compact layer, oxygen can be effectively isolated, and therefore oxidation of SiOC is inhibited.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of nanoporous materials, and in particular to a high-temperature resistant SiOC-SiO2 ceramic nanofiber aerogel and a preparation method thereof. Background Art

[0002] Aerogel is a porous, ultra-light and ultra-high specific surface area material, which is often used in thermal insulation, drug carrier, catalysis, sound insulation, adsorption and other fields. Due to its ultra-low thermal conductivity, it has become the most promising application material in the field of thermal insulation. There are many types of aerogels, mainly including all-carbon aerogel, organic aerogel and ceramic aerogel. Among them, all-carbon aerogel and organic aerogel will inevitably face thermal decomposition problems in high-temperature aerobic environments; while ceramic aerogel has better temperature resistance than the former two, but traditional ceramic aerogels, such as silica aerogel, are prone to crystallization and powderization at high temperatures due to their internal point-to-point connection structure, resulting in structural collapse, which seriously limits their application in extreme high temperature environments. Therefore, the preparation of high-temperature resistant ceramic fiber aerogels is of great practical significance.

[0003] In terms of optimizing the high temperature resistance of aerogels, researchers have also made many attempts. For example, Zhang et al. (ACS Nano 2022, 16, 54875495) used a layer-by-layer stacking method to prepare silica nanofiber membranes into silica fiber aerogels. The aerogel can withstand high temperatures of 1100°C, but when the temperature rises further, the silica fibers will curl due to crystallization, thus destroying the aerogel structure.

[0004] Liu et al. (Nanomaterials 2023, 13(8), 1305) used commercial zirconium dioxide fiber as the aerogel skeleton and aluminoborosilicate as the binder, combined with unidirectional freeze-drying. The prepared zirconia fiber aerogel can withstand high temperatures of 1200°C, but when the temperature rises to 1300°C, the shrinkage rate of the fiber increases sharply, causing its structure to be destroyed.

[0005] Xu et al. (Materials 2022, 15(10), 3522) synthesized silicon carbide nanowires in situ in a mullite fiber preform and prepared a new type of micro / nano composite fiber aerogel by vacuum impregnation and high-temperature pyrolysis. The aerogel can withstand a high temperature of 1400°C, but because silicon carbide will oxidize in high-temperature air, it is difficult for the aerogel to exert its effective performance for a long time in a high-temperature oxygen environment. Summary of the invention

[0006] The purpose of the present invention is to provide a high temperature resistant SiOC-SiO2 ceramic nanofiber aerogel and a preparation method thereof, so as to solve the problems of poor thermal stability, easy decomposition, easy structural collapse and difficulty in application under extremely high temperature (air atmosphere) conditions of conventional aerogels.

[0007] In order to achieve the above object, the present invention adopts the following technical solution:

[0008] The present invention provides a high temperature resistant SiOC-SiO2 ceramic nanofiber aerogel, which is composed of SiOC-SiO2 ceramic nanofibers and a high temperature binder, wherein the SiOC-SiO2 ceramic nanofibers are a SiOC and SiO2 co-embedded composite structure, in which SiOC is formed by a carbon atom replacing an oxygen atom in silicon dioxide, and there is lattice distortion inside.

[0009] In the above technical solution, the silica sol adheres to the surface of SiOC-SiO2 ceramic nanofibers to form a dense layer, which can effectively isolate oxygen, thereby inhibiting the oxidation of SiOC. The preparation method of ceramic nanofiber aerogel includes the following characteristic steps:

[0010] The present invention also provides a method for preparing high temperature resistant SiOC-SiO2 ceramic nanofiber aerogel, comprising the following steps:

[0011] Step 1, tetraethyl orthosilicate and methyltrimethoxysilane are mixed in a molar ratio of 1:0.25-4, deionized water is added, orthophosphoric acid is used as a catalyst, and stirred to prepare a methyl silica sol A with a concentration of 20%;

[0012] Step 2, dissolving polyvinyl alcohol in deionized water to prepare a 10% by mass polyvinyl alcohol aqueous solution, and slowly adding the aqueous solution to the methyl silica sol A obtained in step (1), and stirring to obtain a spinning solution B;

[0013] Step 3, electrospinning the spinning solution B obtained in step (2) to prepare a nanofiber preform, and then placing the nanofiber preform in a high temperature environment and pyrolyzing it to obtain ceramic nanofibers;

[0014] Step 4, tetraethyl orthosilicate is mixed with deionized water, orthophosphoric acid is added as a catalyst, and stirred for 8 hours to prepare a silica sol C with a concentration of 20% by mass;

[0015] Step 5: Disperse the ceramic fibers obtained in step (3) in deionized water, add the silica sol C obtained in step (4) as a binder, mix well, remove moisture by freeze-drying technology to form a freeze-dried preform, and then place the preform in a high temperature environment for calcination to finally obtain a high temperature resistant SiOC-SiO2 ceramic nanofiber aerogel.

[0016] In the above technical solution, the stirring time in step (1) is 6 to 8 hours.

[0017] In the above technical solution, in the spinning solution B in step (2), the mass ratio of the polyvinyl alcohol solution to the methyl silica sol A is 0.9-1.2:1, and the stirring time is 4-6 hours.

[0018] In the above technical solution, during the high-temperature pyrolysis in step (3), the pyrolysis temperature is 1000-1200°C, and the heating rate is 1-5°C / min; the pyrolysis atmosphere is argon or nitrogen or a mixture of the two.

[0019] In the above technical solution, the concentration of the ceramic fiber solution in step (5) is 2 to 8 mg / mL.

[0020] In the above technical solution, the mass ratio of the ceramic fiber solution to the binder in step (5) is 100:0.5-1.

[0021] Because the present invention adopts the above technical means, it has the following beneficial effects:

[0022] 1. The present invention uses methyl silica sol hydrolyzed from tetraethyl orthosilicate and methyltrimethoxysilane to obtain SiOC-SiO2 ceramic nanofibers through electrospinning and pyrolysis. Compared with pure silica nanofibers, SiOC-SiO2 nanofibers have better high temperature resistance. In addition, silica sol is used as a binder to adhere to the fiber surface to form a dense insulating layer, so that the heat resistance temperature of the prepared SiOC-SiO2 ceramic nanofiber aerogel is as high as 1300°C, which can be used for a long time in extremely high temperature environments and has extremely strong oxidation resistance.

[0023] 2. The ceramic fiber preparation method combining sol-gel and electrostatic spinning provided by the present invention has a simple process and a short preparation time, which meets the needs of large-scale production. At the same time, compared with the solid-phase sintering method and the melt spinning method, the sintering temperature is lower during the fiber processing process of the present invention, and the obtained ceramic nanofibers have better uniformity and more cost advantages. In addition, this low-cost preparation method is more in line with the dual-carbon concept, which is of great significance to environmental protection and energy utilization.

[0024] 3. The binder is silica sol. During the aerogel preparation process, silica sol adheres to the surface of SiOC-SiO2 ceramic nanofibers to form a dense layer, which can effectively isolate oxygen and thus inhibit the oxidation of SiOC. The synergistic effect of the two gives SiOC-SiO2 ceramic nanofiber aerogel excellent high temperature resistance and can be used under extremely high temperatures. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1Shown is the preparation flow chart of high temperature resistant SiOC-SiO2 ceramic nanofiber aerogel.

[0026] Figure 2 , Figure 3 Shown is the microscopic morphology of high temperature resistant SiOC-SiO2 ceramic nanofibers.

[0027] Figure 4 Shown is the element distribution diagram of high temperature resistant SiOC-SiO2 ceramic nanofibers. DETAILED DESCRIPTION

[0028] The following is a detailed description of the embodiments of the present invention. Although the present invention will be described and illustrated in conjunction with some specific embodiments, it should be noted that the present invention is not limited to these embodiments. On the contrary, modifications or equivalent substitutions made to the present invention should all be included in the scope of the claims of the present invention.

[0029] In addition, in order to better illustrate the present invention, numerous specific details are given in the following specific embodiments. It will be understood by those skilled in the art that the present invention can also be implemented without these specific details.

[0030] In order to meet the effective application of aerogel in extremely high temperature aerobic environment, based on the above research background, the present invention has made the following innovations to prepare high temperature resistant SiOC-SiO2 ceramic nanofiber aerogel.

[0031] First, a silica sol containing methyl was prepared by the simultaneous hydrolysis of tetraethyl orthosilicate and methyltrimethoxysilane, and ceramic nanofibers with silicon dioxide and silicon oxycarbide interlocked were obtained through processes such as electrospinning and pyrolysis. Since the carbon atom replaces one oxygen atom in the silicon dioxide, the crystallization barrier of silicon dioxide in the fiber becomes larger, making it difficult to crystallize at high temperatures, thereby improving the high temperature resistance of the fiber.

[0032] Second, using silica sol as a high-temperature binder can better cover the fiber surface to form a dense layer. This dense layer can effectively isolate air (oxygen), making silicon oxycarbide more difficult to be oxidized, thereby improving temperature resistance.

[0033] Specifically, the present invention mentions a high temperature resistant SiOC-SiO2 ceramic nanofiber aerogel, which is composed of SiOC-SiO2 ceramic nanofibers and high temperature binders, wherein SiOC-SiO2 ceramic nanofibers are a composite structure of SiOC and SiO co-inlaid, in which SiOC is formed by a carbon atom replacing an oxygen atom in silica, and there is lattice distortion inside, so the structure can effectively inhibit the rapid growth of silica grains at high temperatures and improve the high temperature resistance of aerogels. The binder used is silica sol, and during the aerogel preparation process, silica sol adheres to the surface of SiOC-SiO2 ceramic nanofibers to form a dense layer, which can effectively isolate oxygen, thereby inhibiting the oxidation of SiOC. The preparation method of ceramic nanofiber aerogel includes the following characteristic steps:

[0034] Step (1) Tetraethyl orthosilicate and methyltrimethoxysilane are mixed with deionized water, orthophosphoric acid is added as a catalyst, and stirred to prepare a methyl silica sol A with a concentration of 20%.

[0035] Step (2) dissolving polyvinyl alcohol in deionized water to a concentration of 10% and adding it to the solution A obtained in step (1), stirring to obtain spinning solution B.

[0036] Step (3) The B obtained in step (2) is prepared into nanofibers by electrospinning, and then pyrolyzed at high temperature to obtain ceramic nanofibers.

[0037] Step (4) Tetraethyl orthosilicate is mixed with deionized water, orthophosphoric acid is added as a catalyst, and stirred for 8 hours to prepare a silica sol C with a concentration of 20%.

[0038] Step (5) The ceramic fibers obtained in step (3) are dispersed in deionized water, and C obtained in step (4) is added thereto as a binder. The high temperature resistant SiOC-SiO2 ceramic nanofiber aerogel is obtained by freeze drying and high temperature calcination.

[0039] In the present invention, the molar ratio of tetraethyl orthosilicate to methyltrimethoxysilane in step (1) is 1:0.25-4, preferably 1:0.4-4, and more preferably 1:0.5-4; the stirring time is 6-8h, preferably 6-7h, and more preferably 6-6.5h.

[0040] In the present invention, in the spinning solution B of step (2), the mass ratio of the polyvinyl alcohol solution to the methyl silica sol A is 0.9 to 1.2:1, preferably 1 to 1.2:1, and more preferably 1 to 1.1:1;

[0041] The stirring time is 4 to 6 hours, preferably 4 to 5 hours, and more preferably 4 to 4.5 hours.

[0042] In the present invention, in step (3) high temperature pyrolysis, the pyrolysis temperature is 1000 ~ 1200 ℃, more preferably 1000 ~ 1150 ℃;

[0043] The heating rate is 1 to 5°C / min, preferably 1 to 4°C / min, and more preferably 1 to 3°C / min; the pyrolysis atmosphere is preferably argon or nitrogen, and more preferably argon.

[0044] In the present invention, the concentration of the ceramic fiber solution in step (5) is 2 to 8 mg / mL, preferably 3 to 8 mg / mL, and more preferably 4 to 8 mg / mL;

[0045] The mass ratio of the ceramic fiber solution to the binder is 100:0.5-1, preferably 100:0.6-1, and more preferably 100:0.7-1.

[0046] Example 1

[0047] Step 1: Tetraethyl orthosilicate and methyltrimethoxysilane were mixed in a molar ratio of 1:4 and added into deionized water, and 1 g of orthophosphoric acid was added as a catalyst. The mixture was stirred for 6 hours to prepare a methyl silica sol with a concentration of 20%.

[0048] Step 2: Dissolve polyvinyl alcohol in deionized water to prepare a 10% aqueous solution, and add it to the methyl silica sol obtained in step (1) at a mass ratio of 1:1, and stir for 4 hours to obtain a spinning solution.

[0049] Step 3: The spinning solution is made into nanofibers by electrospinning, and then pyrolyzed at 1100°C in an argon atmosphere at a heating rate of 1°C / min to prepare ceramic nanofibers.

[0050] Step 4: Tetraethyl orthosilicate was mixed with deionized water, 1 g of orthophosphoric acid was added as a catalyst, and the mixture was stirred for 8 h to prepare a silica sol with a concentration of 20%.

[0051] Step 5: The ceramic fibers obtained in step (3) are dispersed in deionized water at a concentration of 8 mg / mL, and the silica sol obtained in step (4) is added thereto as a binder, and the mass ratio of the fiber dispersion to the silica sol is 100:1. After freeze drying and calcination at 900°C in an air atmosphere, a high temperature resistant SiOC-SiO2 ceramic nanofiber aerogel is obtained.

[0052] Example 2

[0053] The difference between Example 2 and Example 1 lies in the molar ratio of tetraethyl orthosilicate to methyltrimethoxysilane and the pyrolysis temperature of the fiber. The molar ratio is changed from 1:4 to 1:2, and the pyrolysis temperature is changed from 1100°C to 1000°C. The other steps are the same.

[0054] Example 3

[0055] The difference between Example 3 and Example 1 lies in the molar ratio of tetraethyl orthosilicate to methyltrimethoxysilane and the pyrolysis temperature of the fiber. The molar ratio is changed from 1:4 to 1:0.5, and the pyrolysis temperature is changed from 1100°C to 1050°C. The other steps are the same.

[0056] Example 4

[0057] The difference between Example 4 and Example 1 lies in the molar ratio of tetraethyl orthosilicate to methyltrimethoxysilane and the pyrolysis temperature of the fiber. The molar ratio is changed from 1:4 to 1:3, and the pyrolysis temperature is changed from 1100°C to 1150°C. The other steps are the same.

[0058] Example 5

[0059] The difference between Example 5 and Example 1 lies in the stirring time and pyrolysis heating rate of the methyl silica sol. The stirring time is changed from 6 h to 6.5 h, and the heating rate is changed from 1° C. / min to 2° C. / min. The other steps are the same.

[0060] The performance of the high temperature resistant SiOC-SiO2 ceramic nanofiber aerogels obtained in Examples 1 to 5 was tested, and the test results are shown in Table 1 below.

[0061] Table 1 Structural parameters and performance test results of high temperature resistant SiOC-SiO2 ceramic nanofiber aerogels of different embodiments

[0062] Example Density (mg / cm3) Thermal conductivity [W / (m·K)] High temperature resistance(℃) Example 1 8.6 0.0275 1300 Example 2 9.2 0.0288 1300 Example 3 8.8 0.0262 1300 Example 4 8.6 0.0253 1300 Example 5 8.9 0.0294 1300

[0063] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

[0064] As can be seen from Table 1, the high temperature resistant SiOC-SiO2 ceramic nanofiber aerogel obtained in the present invention has excellent high temperature resistance, and the effective temperature resistance is 1300° C. The high temperature resistant SiOC-SiO2 ceramic nanofiber aerogel obtained in the present invention has a low density (8.6-9.2 mg / cm3) and a low thermal conductivity of 0.0253-0.0294 W / (m·K).

Claims

1. A high temperature resistant SiOC-SiO2 ceramic nanofiber aerogel, characterized in that: It is composed of SiOC-SiO2 ceramic nanofibers and high-temperature adhesives, wherein the SiOC-SiO2 ceramic nanofibers are a composite structure of SiOC and SiO2 co-embedded. In the composite structure, SiOC is formed by a carbon atom replacing an oxygen atom in silicon dioxide, and there is lattice distortion inside.

2. A high temperature resistant SiOC-SiO2 ceramic nanofiber aerogel according to claim 1, characterized in that: Silica sol adheres to the surface of SiOC-SiO2 ceramic nanofibers to form a dense layer, which can effectively isolate oxygen and thus inhibit the oxidation of SiOC.

3. The method for preparing a high temperature resistant SiOC-SiO2 ceramic nanofiber aerogel according to any one of claims 1 or 2, characterized in that: The steps include: Step 1, tetraethyl orthosilicate and methyltrimethoxysilane are mixed in a molar ratio of 1:0.25-4, deionized water is added, orthophosphoric acid is used as a catalyst, and stirred to prepare a methyl silica sol A with a concentration of 20%; Step 2, dissolving polyvinyl alcohol in deionized water to prepare a 10% by mass polyvinyl alcohol aqueous solution, and slowly adding the aqueous solution to the methyl silica sol A obtained in step (1), and stirring to obtain a spinning solution B; Step 3, electrospinning the spinning solution B obtained in step (2) to prepare a nanofiber preform, and then placing the nanofiber preform in a high temperature environment and pyrolyzing it to obtain ceramic nanofibers; Step 4, tetraethyl orthosilicate is mixed with deionized water, orthophosphoric acid is added as a catalyst, and stirred for 8 hours to prepare a silica sol C with a concentration of 20% by mass; Step 5: Disperse the ceramic fibers obtained in step (3) in deionized water, add the silica sol C obtained in step (4) as a binder, mix well, remove moisture by freeze drying technology to form a freeze dried preform, and then place the preform in a high temperature environment for calcination to finally obtain a high temperature resistant SiOC-SiO2 ceramic nanofiber aerogel.

4. The method for preparing a high temperature resistant SiOC-SiO2 ceramic nanofiber aerogel according to claim 3, characterized in that: The stirring time in step (1) is 6 to 8 hours.

5. The method for preparing a high temperature resistant SiOC-SiO2 ceramic nanofiber aerogel according to claim 3, characterized in that: In the spinning solution B of step (2), the mass ratio of the polyvinyl alcohol solution to the methyl silica sol A is 0.9-1.2:1, and the stirring time is 4-6 hours.

6. The method for preparing a high temperature resistant SiOC-SiO2 ceramic nanofiber aerogel according to claim 3, characterized in that: In step (3), the high-temperature pyrolysis temperature is 1000-1200° C., and the heating rate is 1-5° C. / min. The pyrolysis atmosphere is argon or nitrogen or a mixture of the two.

7. The method for preparing a high temperature resistant SiOC-SiO2 ceramic nanofiber aerogel according to claim 3, characterized in that: The concentration of the ceramic fiber solution in step (5) is 2 to 8 mg / mL.

8. The method for preparing a high temperature resistant SiOC-SiO2 ceramic nanofiber aerogel according to claim 7, characterized in that: The mass ratio of the ceramic fiber solution to the binder in step (5) is 100:0.5-1.

Citation Information

Cited By

  • High-performance ceramic-based composite material for unmanned aerial vehicle as well as preparation method and application thereof

    CN121248329A